2022
DOI: 10.1111/cod.14197
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of late patch test readings in corticosteroid allergy

Abstract: Allergic contact dermatitis (ACD) to corticosteroids remains a diagnostic and therapeutic challenge for the clinicians. Patch testing is the golden diagnostic standard, which is recommended to be read twice, on day (D) 2, D3, or D4 and D7, 1 although some skip the late reading. Previous studies suggest late reading of corticosteroids, 2 but further data are needed. This retrospective study aims to investigate the benefit of day 7 readings. METHODSWe conducted a retrospective study of patients patch tested with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…The group 3 CSs clobetasol‐17‐propionate (in Dermovate) and betamethasone‐17‐valerate (in Betnovate) are frequently used in the treatment of various inflammatory dermatoses such as eczema and cutaneous psoriasis in Denmark. In total, only nine patients sensitised to Group 3 CSs are missed in 1852 patch‐tested patients, and clobetasol‐17‐propionate being a potential Group 3 CS marker, 7,9,20 inclusion of clobetasol‐17‐propionate in consecutively screening panel might optimise the overall sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The group 3 CSs clobetasol‐17‐propionate (in Dermovate) and betamethasone‐17‐valerate (in Betnovate) are frequently used in the treatment of various inflammatory dermatoses such as eczema and cutaneous psoriasis in Denmark. In total, only nine patients sensitised to Group 3 CSs are missed in 1852 patch‐tested patients, and clobetasol‐17‐propionate being a potential Group 3 CS marker, 7,9,20 inclusion of clobetasol‐17‐propionate in consecutively screening panel might optimise the overall sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the clinical relevance of sensitization is based on different clinicians. The intrinsic dual effect of anti‐inflammatory potential and allergenic, inflammatory potential entails challenging patch test readings often being in a spectrum of doubtful to weak positive, thus the experiences of clinicians are important and a delayed patch test reading must happen 20 …”
Section: Discussionmentioning
confidence: 99%
“…Due to this tendency in patch test referral pattern, our results may not reflect the general population of patients with AD. Third, as steroid allergens cause late patch test effects due to their anti-inflammatory effects, additional readings are recommended not only on days 2 and 4 after the patch test, but also on day 7 37 . Indeed, Isaksson et al 38 reported that about 28.6% of cases of budesonide sensitization would be missed without readings on day 7.…”
Section: Discussionmentioning
confidence: 99%
“…antiinflammatoriske effekter, hvorfor senaflaesning af kortikosteroider er saerdeles vigtig [15], men desvaerre spares vaek flere steder i verden.…”
Section: Ugeskrift For Laeger Ugeskrift For Laegerunclassified